Answer :

We have



and


Where x + 2y ≠ 0 and 3x - 2y ≠ 0


Lets simplify these equations. Assuming and



Multiply it with 6, we get


3p + 10q = -9 …(i)


Also,



Multiply it with 20, we get


25p – 12q = 61/3


75 – 36q = 61 …(ii)


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Multiply equation (i) by 36 and equation (ii) by 10, so that the variables p and q in both the equations have same coefficients.


Recalling equations (i) and (ii),


3p + 10q = -9 [×36


75p – 36q = 61 [×10



858p = 286


p = 286/858 = 1/3


Substitute p = 1/3 in eq.(i)/eq.(ii), as per convenience of solving.


Thus, substituting in eq.(i), we get


3(1/3) + 10q = -9


1 + 10q = -9


10q = -9-1 = -10


q = -1


Thus, p=1/3 and q=-1


As p = 1/(x + 2y),



x + 2y = 3 …(iii)


And q = 1/(3x – 2y)



2y – 3x = 1 …(iv)


Subtracting equations (iii) and (iv) to obtain x and y,


(x + 2y) – (2y – 3x) = 3 – 1


x + 2y – 2y + 3x = 2


4x = 2


x = 1/2


Putting the value of x in equation (iv), we get


2y – 3(1/2) = 1


4y – 3 = 2


4y = 2 + 3 = 5


y = 5/4


Hence, we have x=1/2 and y=5/4


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics